Is it necessary to perform routine drainage of the peritoneal cavity after a gastrectomy caused by a neoplasm? - Wroński, Konrad; Okraszewski, Jerzy; Górski, Aleksander; Kunecki, Marek; Bocian, Roman (Contemporary Oncology/Współczesna Onkologia, 2007)
Gastric cancer is one of the most common neoplasms in the world. Surgery is the only effective method of treatment of such a neoplasm. A total or subtotal gastrectomy accompanied by a dissection of the D2 lymph nodes is one of the most technically difficult surgical procedures in oncological surgery. Nowadays in the majority of departments a total or subtotal gastrectomy to treat a neoplasm is performed as open surgery. Also, in most departments it is routine to place a drain or drains in the peritoneal cavity after such surgical procedures so that early complications can be diagnosed. The following article is a review of current knowledge and research concerning routine drainage of the peritoneal cavity after radical surgical procedures due to gastric cancer.